Cranial Bone Lesions in Patagonian Huemul Deer (Hippocamelus bisulcus): First Description of a Neonatal Case - Fluck, Werner Thomas (2022)
The only 350-500 remaining Patagonian huemul deer (Hippocamelus bisulcus) are split into some 50 groups along 2000 km of Andes mountains. Osteopathy occurs among at least 57% of these endangered adult huemul, with 63% of these having mandibular and 100% having maxillary afflictions. We document the first-ever case of a neonate born with advanced cranial osteopathy. Surviving only three days, it was evaluated using computerized tomography. Mandibular wall perforations exposed premolar roots, which has not been described previously in other cervid neonates. This indicates that equivalent lesions found in adults may have started during fetal development likely from nutritional problems, rather than representing secondary effects from postnatal infections. Moreover, high prevalence of such cranial pathology among adults also has not been reported in other cervids. These and additional skeletal lesions would affect predator avoidance, may explain the low average age, and lack of population recovery.